2011
DOI: 10.1016/j.pmrj.2011.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Bupivacaine Injection Leads to Muscle Force Reduction and Histologic Changes in a Murine Model

Abstract: Although our results do not allow a direct clinical application, we believe that caution should be warranted when intramuscular bupivacaine is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…6) caused by the surgically-induced injury. Our results corroborate previous data reported in a toxin-induced muscle injury rat model, where a 37 % decrease in Tetanic force was described in rat gastrocnemius muscle 2 weeks after injury induced by intramuscular bupivacaine injection [24]. In summary, this study presents a new model of surgicallyinduced skeletal muscle injury in rats, which mimics the complete process of necrosis and regeneration observed in muscle injuries and reproduces very closely the most frequent skeletal muscle lesions observed in sports human clinics.…”
supporting
confidence: 91%
“…6) caused by the surgically-induced injury. Our results corroborate previous data reported in a toxin-induced muscle injury rat model, where a 37 % decrease in Tetanic force was described in rat gastrocnemius muscle 2 weeks after injury induced by intramuscular bupivacaine injection [24]. In summary, this study presents a new model of surgicallyinduced skeletal muscle injury in rats, which mimics the complete process of necrosis and regeneration observed in muscle injuries and reproduces very closely the most frequent skeletal muscle lesions observed in sports human clinics.…”
supporting
confidence: 91%
“…To make an animal model which will explain the correlation between the paraspinal muscle injury and kyphosis, we have reviewed the muscle injury models introduced to date. The bupivacaine is the most widely used material, the injection of bupivacaine weakens the strength of skeletal muscles and this induces the necrosis of muscle fibers in histology 17) . Besides, it was reported that venom phospholipases A2 induces the necrosis of skeletal muscle 9) .…”
Section: Discussionmentioning
confidence: 99%
“…In rabbit studies, 8 to 10% lidocaine has been demonstrated to be neurotoxic [22, 23]. The other local anesthetic, bupivacaine, has been shown to be degenerative [24] and to decrease muscle function [25] in rats. These studies also showed that, over time, bupivacaine was not completely destructive but had some regenerative and healing effects.…”
Section: Discussionmentioning
confidence: 99%